2010
DOI: 10.3810/pgm.2010.03.2118
|View full text |Cite
|
Sign up to set email alerts
|

LDL-C Goal Attainment in Patients who Remain on Atorvastatin or Switch to Equivalent or Non-equivalent Doses of Simvastatin: A Retrospective Matched Cohort Study in Clinical Practice

Abstract: Continuing atorvastatin was associated with lower LDL-C levels and better LDL-C target attainment compared with switching to simvastatin. Patients switched to an equivalent simvastatin dose had lower LDL-C levels and were more likely to achieve LDL-C targets than patients switched to a non-equivalent dose, suggesting physicians must consider dosage equivalence when switching statins, and should measure LDL-C and titrate statins as necessary to achieve LDL-C control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 21 publications
(16 reference statements)
1
15
0
Order By: Relevance
“…Similar to our findings, a recent US study by Rublee and Burke [14] noted that among 1048 patients who were switched from atorvastatin to simvastatin, switching was from a mean daily dose of 20.9 mg (±15.3) to a mean daily dose of 32.6 mg (±17.9).…”
Section: Discussionsupporting
confidence: 80%
“…Similar to our findings, a recent US study by Rublee and Burke [14] noted that among 1048 patients who were switched from atorvastatin to simvastatin, switching was from a mean daily dose of 20.9 mg (±15.3) to a mean daily dose of 32.6 mg (±17.9).…”
Section: Discussionsupporting
confidence: 80%
“…However, negative views regarding the quality, safety, and efficacy of generic drugs persist among some patients, which may hinder compliance to these medications . Furthermore, replacing a branded statin with the generic of another statin (i.e., therapeutic substitution) has been associated with potentially inadvertent dose decreases or increases . Accordingly, to optimize patient compliance with statin therapy, we need to better understand the impact of switching from branded to generic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, these results are consistent with previous findings after highefficacy statin switches to equivalent or lower efficacy doses of simvastatin. [20][21][22]29,30 Overall, this study illustrates how increased generic use without careful consideration of patient risk factors and current therapy can lead to switches to less efficacious dosages, higher LDL-C levels, and lower goal attainment rates. This information may help to inform physicians when considering therapeutic options.…”
Section: Discussionmentioning
confidence: 99%
“…18 The likelihood of LDL-C goal attainment has been observed to be lower on less efficacious versus higherefficacy statins in diabetic patients, 19 as in other populations. 10,[20][21][22] The National Committee for Quality Assurance has reported that the rates of LDL-C goal attainment (,100 mg/dL) in 2007 (change from 2006) in participating U.S. managed care plans, Medicare, and Medicaid for diabetes patients were 43.8% (10.8), 46.8% (20.1), and 31.3% (10.7), respectively. 23 It is worth noting that the rates of LDL-C control have remained stable or decreased slightly for diabetics during 2005 to 2007, possibly reflecting switches to less efficacious simvastatin doses.…”
Section: Discussionmentioning
confidence: 99%